Analysis Implementation Of Accounting Information System To Financial Reports Of Small And Medium Enterprises - I Nyoman SUTAPA; Ni Luh Putu Mita MIATI (Indonesia Strategic Sustainability, 2020)
MSMEs are required to be able to provide information related to financial position and changes in financial position that are useful in making decisions. Based on the results of interviews, several small and medium enterprises in the city of Denpasar still experience difficulties in preparing financial reports for the purposes of measuring the performance of small and medium enterprises. A good accounting information system is needed to facilitate MSMEs in preparing financial reports, one of which is for the purposes of measuring the performance of MSMEs. in this study will examine the effect of the application of accounting information systems and company categories on the ability to compile financial reports of small and medium enterprises in BALI, Denpasar city. The sample in the study amounted to 100 MSMEs. The data analysis technique used Partial Least Square (PLS) analysis. As a result, the application of the accounting information system has a positive effect on the ability to measure the performance of small and medium enterprises in Denpasar, Bali and the category of small and medium enterprises has no effect on the ability to measure the performance of small and medium enterprises in Denpasar. the city of BALI.